PERAN SEMANGAT KERJA MEMEDIASI PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS KESEHATAN KABUPATEN TABANAN, BALI - Ni Made Dewi Kansa Putri (Widya Manajemen, 2019)
The government to provide the excellent public service performance must supported by existing resources. Human factors or man power are an important part of an organization, where talented, qualified human resources are needed, willing to cooperate with teams and have high spirit. Work spirit is needed in every employee cooperation effort to achieve organizational goals, because with the work spirit will result in high performance for the organization. Besides that, employee performance is also determined by the work environment both physical and non-physical. This study aims to analyze the influence of the work environment and work spirit on the performance of employees at the Tabanan District Health Office. Research uses Path Analysis as a method of data analysis, where data collection is done by observation, interviews, literature studies, and questionnaires. As the initial stage of the analysis, a validity and reliability test will be carried out on the research instrument. The results showed that the work environment and work spirit had a positive and significant effect on employee performance at the Tabanan District Health Office. Where the work spirit variable acts as an mediation variable in the influence of the work environment on employee performance at the Tabanan District Health Office.